Sindrom Horor Media Sosial: Kecemasan Kolektif, Ketakutan Mistis Digital, dan Reorientasi Pendidikan Islam - Taufikur Rohman; Nasrudin Nasrudin; Mohammad Rifan Firmansyah; Aminuddin Aminuddin; Herdian Mainaki (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
The widespread circulation of horror content on social media has transformed mystical narratives into digital experiences capable of shaping public perception, emotions, and behavior. This study examines the emergence of collective anxiety and digital mystical fear generated by horror content and explores its implications for Islamic education. Employing a qualitative approach through library research and netnography, the study analyzes theological, psychological, and neuroscientific literature concerning fear, perception, and supernatural beliefs, while netnography investigates users' responses to horror-related content on YouTube and TikTok. The findings reveal that many experiences perceived as supernatural can be explained through psychological and neurological mechanisms, including pareidolia, priming effects, and hyper-arousal. From an Islamic theological perspective, satanic influence primarily operates through suggestion (was-was) rather than direct physical intervention. Furthermore, the amplification of horror content through social media algorithms contributes to collective anxiety, sleep disturbances, restricted daily activities, and declining productivity. Accordingly, this study proposes an Integrative Islamic Education framework that combines digital media literacy with Tauhid-based spiritual literacy to strengthen critical thinking, reinforce sound theological understanding, and mitigate irrational fear in contemporary digital society.